Influência de diferentes combinações de lâminas de eucalyptus saligna e Pinus taeda em painéis estruturais LVL - Müller, Marcos Theodoro (2009)
This research aimed at investigating the influence of the positioning of Eucalyptus saligna and Pinus taeda wood veneers on the layers composing the Laminated Veneer Lumber (LVL) structural panels. The panels were manufactured in six different combinations of five veneers of 3,2 mm, glued with phenol-formaldehyde, resulting in treatments constituted of wood of the same species or with a composition of the two wood types. The evaluation of the proposed combinations was performed under the characterization of physical properties (moisture content, density, water absortion, thickness swelling and volumetric expansion) and mechanical properties verified in flatwise and edgewise static bending (modulus of elasticity, stress at the proportional limit and modulus of rupture). The quality of the adhesive wood bonding was evaluated through the glue line shear strength by compression loading and the percentage of wood failure. Wood bonding tests were done with wood of the same species and wood of two studied types. The results obtained indicated that, in most situations, the different positionings of the veneers with larger density (in the outer, intermediate and inner layers) influenced the mechanical properties of the panels. The influence detected was varied, especially for MOE and MOR when comparing the flatwise and edgewise experimented positions. In certain positions, in the layers of the LVL compositions, the presence of eucalypt veneers resulted in stiffness and strength increases. In dry shear the resistances of the joints were shown to be equivalent; after boiling, the joints in eucalypt veneers presented larger strength. The percentage of wood failure was above 80% (in eucalypt veneers) and above 90% (in pine and mixed veneers) and maintained stable after boiling, indicating good gluing quality for all the tested wood bondings. However, it was verified that the adhesive wood bonding of eucalypt and pine was shown more reliable than the bonding between eucalypt veneers. Therefore, the treatments formed by interposed veneers of eucalypt and pine presented a better combination of performance and reliability for the properties of stiffness, strength and adherence.